Influence of ovarian location and dimensions in some characteristics of follicle and oocyte in Iraqi cows - Hassan, Fawzia J.; Abood, Hashim M.; Hassan, Mayada S. (Journal of Kerbala for Agricultural Sciences, 2016)
The research was designed to study the Influence of ovarian side in alternation it's dimensions and some follicular and oocyte in Iraqi cows. The study was carried out at the laboratories of Animal Production Techniques Department, Al-Musiab Technical College during the period from September 2015 to April 2016., The ovaries were excised from 60 Iraqi cows slaughtered at abattoirs of Babylon province and transported to the laboratory within 2 hours. The length, width and thickness of the ovaries were measured using vernier calipers. The follicles on each ovary were counted and their diameters was measured and grouped into three categories, small (3-5mm), medium (6-10mm) and large (11-20mm). The follicular fluid was aspirated and to put into Petri dish for oocytes recovered. The oocytes were examined under a stereoscope (x10) for their diameters measured. The results showed that the average of oocyte diameter was significantly (P<0.05) increased with increasing of follicular diameter in the right and left ovaries. The length, width and thickness of the left ovary was significantly higher (P<0.05) compared with right ovary. The results also showed that the regression coefficient of length and width of the ovary on oocyte diameter was negative and significant (P<0.05) and to reach – 0.079 and – 0.926 respectively , and the regression of ovarian thickness on follicular diameter , number of follicle and oocyte diameter were negative and significant (P<0.05) and to reach – 0.047 , -0.023 and 0.624 respectively. The correlation coefficient between ovarian length and it's width, thickness and the number of follicle on each ovary was positive and significant (P<0.05) and to reach 0.17 , 0.19 and 0.22 respectively , while this correlation was negative and significant (P<0.05), between ovarian length and follicular diameter and to reach 0.29 and 0.24 respectively. The correlation between width of ovary and it's thickness and number of follicles on each ovary was positive and highly significant (P<0.01). In conclusion , possibility to using oocyte diameter as selection indicator, and selection of oocytes through the dimensions of the ovary.